Bone metastasis and pain research through the dual lens of bibliometrics and bioinformatics: knowledge structure, frontiers, and core pathway analysis (2015–2024) - Meng, Linghan; Tao, Jingna; Zheng, Guangda; Ren, Juanxia; Shang, Lu; Li, Dongtao; Liu, Haixiao; Bao, Yanju; Hua, Baojin (Frontiers in Medicine, 2025)
BackgroundCancer-induced bone pain (CIBP) represents a formidable clinical challenge with complex mechanisms, and existing treatments remain unable to effectively control pain in many patients. This study combined bibliometric and bioinformatic approaches to delineate key research trends, principal themes and future directions in the field of bone metastasis and pain research over the past decade (2015–2024).MethodsWe selected 1,822 relevant documents from the Web of Science Core Collection for bibliometric analysis to identify major research characteristics, collaboration networks and emerging trends. Additionally, we employed bioinformatic methods to screen core genes associated with both bone metastasis and cancer pain, and analysed their functions and signalling pathways.ResultsResearch output and academic influence demonstrated an upward trajectory, with the United States and China being the countries with the highest publication volumes. Research hotspots are shifting from traditional palliative treatments towards precision therapies, with stereotactic body radiotherapy, minimally invasive ablation techniques and neuropathic pain mechanisms representing major research frontiers. Bioinformatic analysis identified core hub genes such as TP53 and EGFR, and revealed significant enrichment of signalling pathways including PI3K-Akt, MAPK and TNF in the common pathological processes of bone metastasis and pain.ConclusionThis study, for the first time combining both methodologies, revealed the field’s evolution from traditional treatments towards precision interventions and mechanistic exploration. The molecular targets and signalling pathways we identified provide promising directions for developing novel therapies capable of simultaneously controlling tumour progression and alleviating pain.